1966
DOI: 10.21236/ad0644054
|View full text |Cite
|
Sign up to set email alerts
|

The Design of Instructional Systems

Abstract: I TO-1. This report was prepared to provide general guidelines for a system approach to the design of training programs, in order to develop programs that will be maximally effective and yet operate at minimum cost.2. The report is based on an exte nsive literature survey and upon training research which has been conducted by thef~iHuman Resources Research Office. Instructional system componients which ar-e disc~ussed include presentation of information, practice techniques, st'udent mianagement, quality contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1969
1969
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…They had been receiving HumRRO technical reports on individual development projects and had frequent contact with HumRRO personnel who did a good deal of persuasion and selling of the technology. As a specific effort at transfer, three special publications were prepared by Robert G. Smith, The Development of Training Objectives (1964), Controlling the Quality of Training (1965) and The Design of Instructional Systems (1966).…”
Section: Technologymentioning
confidence: 99%
“…They had been receiving HumRRO technical reports on individual development projects and had frequent contact with HumRRO personnel who did a good deal of persuasion and selling of the technology. As a specific effort at transfer, three special publications were prepared by Robert G. Smith, The Development of Training Objectives (1964), Controlling the Quality of Training (1965) and The Design of Instructional Systems (1966).…”
Section: Technologymentioning
confidence: 99%
“…References of aid in clarifying these concepts are Shoemaker's (14) article on the functional context method, Chapter 5 of Smith's volume on The Design of Instructional Systems (15), and an address by McClelland (16).…”
Section: Organization and Sequence Of Instructional Contentmentioning
confidence: 99%
“…Training techniques and devices, achievement and proficiency teAts, and graduate performance specifications may all be unified in terms of precisel) stated training objectives. The generation of training content is discussed in Smith (33). Quality control of training content is discussed in Smith (34), and example of research on development of quality contrC meassires may be found in Greer et al (35) and a supplemental report by Duffy and Colgan (36).…”
Section: Develop Training Programmentioning
confidence: 99%